Characteristics of Gut Microbial Profiles of Offshore Workers and Its Associations With Diet - Zhang, Chunhong; Liang, Dong; Li, Xiaoxue; Liu, Jun; Fan, Mengya; Jing, Mei; Wang, Yifei; Zhang, Yu; Fang, Yiqun; Li, Dan (Frontiers in Nutrition, 2022)
Composition of gut microbiota is not a static state in human but fluctuates in response to changes in environments, diet and lifestyle factors. Here, we explored differences of gut microbiota between populations worked at offshore and onshore, and further studied microbiota-associated variables in offshore workers. We investigated the gut microbiota of 168 healthy subjects (offshore: 145, onshore: 23) using 16S rRNA sequencing. Our results indicated that marine environment caused significant changes in intestinal microbial structure, which was mainly reflected in the increase of bacterial diversity, changes of composition, and emergence of more specific bacteria in offshore workers (OFWs). In addition, characteristics of gut microbiota in OFWs were further explored, and genus Holdemanella was considered as a potential contributor to stable state of health. Besides, some dietary factors including duck, mutton, dairy products and algae vegetables were identified as the gut microbial covariates in the OFWs cohort, and were positively correlated with genus Holdemanella. Which suggesting the positive intervention of diet on Holdemanella. Our data highlight, for the first time to our knowledge, that marine geographical environment plays an important role in shaping the gut mycobiome composition. And diet could be considered as the targeted interventions that alter the composition of the microbiome to improve host health.